2016
DOI: 10.1021/acssynbio.5b00191
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Binding and Site-Directed Labeling of Biosilica-Immobilized Fusion Proteins Expressed in Diatoms

Abstract: The diatom Thalassiosira pseudonana was genetically modified to express biosilica-targeted fusion proteins comprising either enhanced green fluorescent protein (EGFP) or single chain antibodies engineered with a tetracysteine tagging sequence. Of interest were the site-specific binding of (1) the fluorescent biarsenical probe AsCy3 and AsCy3e to the tetracysteine tagged fusion proteins and (2) high and low molecular mass antigens, the Bacillus anthracis surface layer protein EA1 or small molecule explosive tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 30 publications
(71 reference statements)
2
30
0
Order By: Relevance
“…Moreover, newly developed fluorescent proteins compatible with a biosilica embedded photo-conversion mechanism may further increase the resolution and thus allow more insights in the underlying protein pattern. Structured illumination microscopy studies showed that biarsenic Cyanine fluorophores (AsCy3 and AsCy3e) can be further used for silica embedded fusion proteins and are due to their blinking nature also potentially suited for single-molecule localization microscopy1348. We further anticipate that the use of multicolor PALM and colocalization studies49 will allow deeper insights in protein-protein interactions during silica biogenesis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, newly developed fluorescent proteins compatible with a biosilica embedded photo-conversion mechanism may further increase the resolution and thus allow more insights in the underlying protein pattern. Structured illumination microscopy studies showed that biarsenic Cyanine fluorophores (AsCy3 and AsCy3e) can be further used for silica embedded fusion proteins and are due to their blinking nature also potentially suited for single-molecule localization microscopy1348. We further anticipate that the use of multicolor PALM and colocalization studies49 will allow deeper insights in protein-protein interactions during silica biogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Fluorescence microscopy, on the other hand, allows live cell imaging and direct access to simultaneous multi-color and thus multi-protein visualization. Recently, structured illumination microscopy with its resolution of up to 150 nm has been applied to localize fusion proteins inside diatoms13. Yet, single-molecule localization microscopy (SMLM) which extends the range of fluorescence microscopy to spatial resolutions in the tens of nanometer regime1415, has not been applied to diatoms.…”
mentioning
confidence: 99%
“…Ford et al expanded the repertoire of recombinant proteins that can be genetically immobilized in diatom biosilica, including single‐chain antibodies for binding both large‐ and small‐molecule antigens with applications in environmental sensing and therapeutics or tetracysteine‐tags for site‐specific affinity labeling . To address these issues, T. pseudonana was transformed with silica‐targeting expression vectors encoding single‐chain antibodies.…”
Section: Functionalization Of Diatom Frustules By Geneticsmentioning
confidence: 99%
“…The diatom Thalassiosira pseudonana is a model organism for in vivo self-assembly of genetically-modified frustules. As such, a number of proteins successfully have been used to functionalize the biosilica frustule of this diatom species [15][16][17][18]. Recent efforts in our lab focused on functionalization of the biosilica of T. pseudonana with chimeric fusion proteins consisting of the diatom-derived silica targeting peptide Sil3 T8 [15,16] and a small synthetic antibody derivative (e.g., a single-chain variable fragment, scFv, or a single domain antibody, sdAb) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…As such, a number of proteins successfully have been used to functionalize the biosilica frustule of this diatom species [15][16][17][18]. Recent efforts in our lab focused on functionalization of the biosilica of T. pseudonana with chimeric fusion proteins consisting of the diatom-derived silica targeting peptide Sil3 T8 [15,16] and a small synthetic antibody derivative (e.g., a single-chain variable fragment, scFv, or a single domain antibody, sdAb) [18,19]. Functionalization of T. pseudonana biosilica with an sdAb against the surface layer (S-layer) protein extractable antigen 1 (EA1) of Bacillus anthracis [18] by in vivo self-assembly utilized sdAb EA1 , clone A1, which recognizes an epitope of EA1 accessible in lysed spores [20].…”
Section: Introductionmentioning
confidence: 99%